2011
DOI: 10.1021/ci2000506
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively Interpreted Enhanced Inhibition of Cytochrome P450s by Heteroaromatic Rings Containing Nitrogen

Abstract: It has been known for a long time that certain substructures bind to the heme iron in cytochromes P450. Detection of spectroscopic changes and crystal structures of protein ligand complexes have provided qualitative evidence, including for aromatic nitrogen-containing ligands. Compounds containing these same substructures are more likely to inhibit cytochrome P450s than expected due to lipophilicity. These two sets of observations are not easily linked by experiment, because binding to the iron atom alone is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 66 publications
3
25
0
Order By: Relevance
“…Some N-containing aromatic heterocycles can interact strongly with the ferric haem 20 21 and the semi-covalent bond formed between the haem iron and aromatic nitrogen atom can only be described accurately by methods that explicitly consider electrons 17 . Density functional theory (DFT) methods have been successfully applied to describe this bond type and to calculate interaction energies between the haem iron and aromatic aza-rings 17 21 22 . The binding energy was calculated for the interaction of the most common sp 2 -hybridized N-containing rings with the haem using the DFT method according to the scheme shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some N-containing aromatic heterocycles can interact strongly with the ferric haem 20 21 and the semi-covalent bond formed between the haem iron and aromatic nitrogen atom can only be described accurately by methods that explicitly consider electrons 17 . Density functional theory (DFT) methods have been successfully applied to describe this bond type and to calculate interaction energies between the haem iron and aromatic aza-rings 17 21 22 . The binding energy was calculated for the interaction of the most common sp 2 -hybridized N-containing rings with the haem using the DFT method according to the scheme shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The link between the energies calculated here and those described previously is uncertain, [25] but it was previously observed that binding energiesb elow about À5kcal/mol correspond to enhanced inhibition.T he calculations suggest that the anionic form binding to the heme iron in am onodentate fashion, as shown in Figure 8, is dominant. When the two ligand oxygena toms were presented to the iron atom at the beginning of ag eometry optimization, one always dissociated leaving am onodentate interaction.…”
Section: Special Issue United Kingdommentioning
confidence: 46%
“…Previous studies show that quantum mechanical calculations can indicate which compoundsa re likely to bind directly to the iron atom. [25,26] These calculations employ B3LYP/6-31G* and have iron in its Fe 3 + doublet state( with iron having lanl2dz basis set and pseudopotential). [27,28] The structures includet he iron atom,i ts porphyrin ligand and methyl thiolate anion whichm imics the cysteine that links the hemet ot he protein.…”
Section: Special Issue United Kingdommentioning
confidence: 99%
See 1 more Smart Citation
“…Solvation effects were calculated at the same level of theory with the continuum conductor-like screening model (COSMO) and an effective dielectric constant () of 4 (Klamt and Schuurmann, 1993). The binding energies reported in Table 3 were given as difference between the energy of the complex between the heme and the molecular fragment and the water-fragment contributions as previously described (Leach and Kidley, 2011). All the calculations were performed in the doublet spin state using the TURBOMOLE software (TURBOMOLE, 2011).…”
Section: Fe-n Binding Energy Calculationsmentioning
confidence: 99%